Analysis of growth dynamics in five different media and metabolic phenotypic characteristics of Piriformospora indica - Hu, Jing-rong; Li, Jin-meng; Wang, Hai-yan; Sun, Mei-li; Huang, Chun-yang; Wang, Han-cheng (Frontiers in Microbiology, 2024)
Piriformospora indica is an important endophytic fungus with broad potential for alleviating biotic and abiotic stress on host plants. This study monitored the growth dynamics of P. indica on five commonly used artificial media of microorganisms and analyzed its metabolic characteristics applying Biolog Phenotype Microarray (PM) technology. The results showed that P. indica grew fastest on Potato Dextrose Agar (PDA), followed by Kidney Bean Agar (KBA), Alkyl Ester Agar (AEA), Oatmeal Agar (OA), and Luria-Bertani agar (LB), and the most suitable medium for spore production was OA. Using Biolog PM1-10, 950 metabolic phenotypes of P. indica were obtained. P. indica could metabolize 87.89% of the tested carbon sources, 87.63% of the tested nitrogen sources, 96.61% of the tested phosphorus sources, and 100% of the tested sulfur sources. P. indica displayed 92 kinds of tested biosynthetic pathways, and it could grow under 92 kinds of tested osmotic pressures and 88 kinds of tested pH conditions. PM plates 1-2 revealed 43 efficient carbon sources, including M-Hydroxyphenyl acid, N-Acetyl-D-Glucosamine, Tyramine, Maltotrios, α-D-Glucosine, I-Erythritol, L-Valine, D-Melezitose, D-Tagatose, Turanose, etc. PM plates 3,6-8 indicated 170 efficient nitrogen sources, including Adenosine, Inosine Allantoin, D, L-Lactamide, Arg-Met, lle-Trp, Ala-Arg, Thr-Arg, Trp-Tyr, Val-Asn, Gly-Gly-D-Leu, Gly-Gly-Phe, Leu-Leu-Leu, etc. This research demonstrates that P. indica can metabolize a variety of substrates such as carbon and nitrogen sources, and has a wide range of environmental adaptability. The growth dynamics on artificial culture media and metabolic phenotypes of P. indica can be used to investigate its biological characteristics, screen more suitable growth and sporulation conditions, and elucidate the physiological mechanisms that enhance the stress resistance of host plants. This study provides a theoretical basis for its better application in agriculture.